Bronchoscopy in lung cancer: navigational modalities and their clinical use - Herth, Felix; Eberhardt, Ralf; Schuhmann, Maren (Expert review of respiratory medicine, 2016)
Introduction: More than 150,000 solitary pulmonary nodules are reported each year in the United States. As the popularity of low dose CT scan use for screening grows, these numbers are likely to increase substantially over the coming years. More than 10 million CT scans of the chest were performed in the United States alone in 2012, highlighting the potential for this clinical scenario. Detecting a nodule on either a chest radiograph or a CT scan frequently leads to a cascade of further investigations to establish a definite diagnosis. Thoracic surgery is frequently performed to obtain a tissue diagnosis in these cases, however, for what often turns out to be a benign abnormality.Areas covered: During the last decade, several new technologies have been introduced to the field of bronchoscopy. As experience with these technologies has increased, the body of published literature has grown.Expert commentary: In this review, we assess the most important and interesting articles in the field. The value and the limitations of the various options will be discussed based on the actual evidence.
Gesehen am 13.05.2020